Who was Abraham Lincoln? - Pascal, Janet B; Illustrated by O'Brien, John (New York Penguin Workshop, 2008)
Who was Abraham Lincoln? A boy who only had a year of schooling? A practical joker? One of the greatest presidents ever? All of the above! Find out more about the real Abraham Lincoln in this illustrated biography.
Include Illustration and Bibliography
Keywords: United States -- Presidents